7x + 8y
the answer to this problem is -2x^2y^2
y^2 + 7y + 12 = (y+4)(y+3)
7y+3x-21 =0 7y = -3x+21 y = -3/7x+3 The y intercept is 3
To expand the expression 7x(7y) using the distributive property, you distribute the 7x to both terms inside the parentheses. This results in 7x * 7y = 49xy. The distributive property allows you to multiply each term inside the parentheses by the term outside the parentheses, simplifying the expression.
7x + 8y
the answer to this problem is -2x^2y^2
y^2 + 7y + 12 = (y+4)(y+3)
7y+3x-21 =0 7y = -3x+21 y = -3/7x+3 The y intercept is 3
The GCF is 7.
8y + 7y = 15ySo [ 8y + 9 + 7y ] = 15y + 9If you want to get fancy and factor that expression, it's 3(5y + 3) .
To expand the expression 7x(7y) using the distributive property, you distribute the 7x to both terms inside the parentheses. This results in 7x * 7y = 49xy. The distributive property allows you to multiply each term inside the parentheses by the term outside the parentheses, simplifying the expression.
(y + 5) (y + 2)
(x + 5y)(x + 7y)
7(y + 4)
-8(x - 7y)(x + 2y)
5x(6x + 7y + 8)